Parameters affecting the selectivity of an electrical insecticide - Lahouaria Neddar; Samir Flazi (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Using an electrical approach in the field of agriculture can be considered as one of the solutions in order to control harmful flying insects. This technique is based on the use of a bio and selective electrical insecticide whose principle consists in attracting insects by the light then get them electrocuted by an electrical discharge. Moreover, There are several parameters that affect the selectivity of electrical insecticide such as: the light, the most efficient, the inter electrode distance, where the insect is exterminated, and the electric current that passes through the insect’s body. In this paper, a simulation study was carried out concerning the distribution of the electric field between two electrodes in presence of particle conductor while focusing on the different body sizes. On the other hand, an experimental study was conducted on live locusts to determine the effect of electrical current on insect’s body taking into account the voltage and frequency. Finally, the results are discussed and analyzed in this paper.